The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/00909882.2014.982682
|View full text |Cite
|
Sign up to set email alerts
|

Disasters and Information Source Repertoires: Information Seeking and Information Sufficiency in Postearthquake Haiti

Abstract: This study examines how Haitians used "information source repertoires" to meet information insufficiencies following the 2010 earthquake. Using survey data gained in Haiti, the study explores which demographic and structural factors predicted the number of sources used and combinations of information sources following the disaster. Analysis of the data revealed two distinct repertoires of information sources: a "traditional" repertoire of radio, TV, church, and word of mouth; and an "elite" repertoire of newsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 49 publications
1
28
2
Order By: Relevance
“…The finding that females reported that they would use more sources for gathering information about a hurricane evacuation is counter to findings by Sommerfeldt (), in which ‘Men were more likely to spend more time using information sources… and have a larger range of daily information sources than women’ (p. 11). Although we did not ask participants the amount of time they would spend gathering information, we found that men tended to report that they would rely on fewer information sources.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…The finding that females reported that they would use more sources for gathering information about a hurricane evacuation is counter to findings by Sommerfeldt (), in which ‘Men were more likely to spend more time using information sources… and have a larger range of daily information sources than women’ (p. 11). Although we did not ask participants the amount of time they would spend gathering information, we found that men tended to report that they would rely on fewer information sources.…”
Section: Discussioncontrasting
confidence: 81%
“…The finding that females reported that they would use more sources for gathering information about a hurricane evacuation is counter to findings by Sommerfeldt (2015), in which 'Men were more likely to spend more time using information sources. .…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The literature on the warning-response process recommends disseminating warning messages through multiple channels to aid preparedness behaviour (Sharma et al, 2009;Sheppard, Janoske, and Liu, 2012). The work of Sommerfeldt (2015) revealed that people variously used the internet, newspapers, radio, short message service (SMS), television, and word of mouth to gather information after the devastating earthquake in Haiti on 12 January 2010. The model of information repertoires proposes that individuals use different sources (such as interpersonal communication, newspapers, or television) to obtain information on a topic of interest (Reagan, 1996).…”
Section: Information Repertoires and Disaster Preparednessmentioning
confidence: 99%
“…Research has shown that demographic factors such as age, education, and sex are predictors of risk information seeking in routine and non-routine situations, as well as of disaster preparedness (see, for example, O'Keefe, Ward, and Shepard, 2002;Spence, Lachlan, and Burke, 2008;Perreault, Houston, and Wilkins, 2014;Sommerfeldt, 2015;Kirschenbaum, Rapaport, and Canetti, 2017). Research has shown that demographic factors such as age, education, and sex are predictors of risk information seeking in routine and non-routine situations, as well as of disaster preparedness (see, for example, O'Keefe, Ward, and Shepard, 2002;Spence, Lachlan, and Burke, 2008;Perreault, Houston, and Wilkins, 2014;Sommerfeldt, 2015;Kirschenbaum, Rapaport, and Canetti, 2017).…”
Section: Demographic and Geographical Factorsmentioning
confidence: 99%